The natural compound Jatrophone interferes with Wnt/β-catenin signaling and inhibits proliferation and EMT in human triple-negative breast cancer - Fatima, Iram; El-Ayachi, Ikbale; Taotao, Ling; Lillo, M Angeles; Krutilina, Raisa I; Seagroves, Tiffany N; Radaszkiewicz, Tomasz W; Hutnan, Miroslav; Bryja, Vitezslav; Krum, Susan A; Rivas, Fatima; Miranda-Carboni, Gustavo A (PloS one, 2017)
Metastatic breast cancer is the leading cause of worldwide cancer-related deaths among women. Triple negative breast cancers (TNBC) are highly metastatic and are devoid of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) amplification. TNBCs are unresponsive to Herceptin and/or anti-estrogen therapies and too often become highly chemoresistant when exposed to standard chemotherapy. TNBCs frequently metastasize to the lung and brain. We have previously shown that TNBCs are active for oncogenic Wnt10b/β-catenin signaling and that WNT10B ligand and its downstream target HMGA2 are predictive of poorer outcomes and are strongly associated with chemoresistant TNBC metastatic disease. In search of new chemicals to target the oncogenic WNT10B/β-CATENIN/HMGA2 signaling axis, the anti-proliferative activity of the diterpene Jatrophone (JA), derived from the plant Jatropha isabelli, was tested on TNBC cells. JA interfered with the WNT TOPFLASH reporter at the level between receptor complex and β-catenin activation. JA efficacy was determined in various subtypes of TNBC conventional cell lines or in TNBC cell lines derived from TNBC PDX tumors. The differential IC50 (DCI50) responsiveness was compared among the TNBC models based on etiological-subtype and their cellular chemoresistance status. Elevated WNT10B expression also coincided with increased resistance to JA exposure in several metastatic cell lines. JA interfered with cell cycle progression, and induced loss of expression of the canonical Wnt-direct targets genes AXIN2, HMGA2, MYC, PCNA and CCND1. Mechanistically, JA reduced steady-state, non-phosphorylated (activated) β-catenin protein levels, but not total β-catenin levels. JA also caused the loss of expression of key EMT markers and significantly impaired wound healing in scratch assays, suggesting a direct role for JA inhibiting migration of TNBC cells. These results indicate that Jatrophone could be a powerful new chemotherapeutic agent against highly chemoresistant triple negative breast cancers by targeting the oncogenic Wnt10b/β-catenin signaling pathway.
Keywords: apoptóza; epitelo-mezenchymální tranzice; Epithelial-Mesenchymal Transition; lidé; proteiny Wnt; beta-katenin; Cell Proliferation; Apoptosis; Cell Line, Tumor; Signal Transduction; Humans; Diterpenes; proliferace buněk; signální transdukce; diterpeny; triple-negativní karcinom prsu; Wnt Proteins; nádorové buněčné linie; beta Catenin; Triple Negative Breast Neoplasms